Transforming Islamic Religious Education in Indonesia: A Socio-Historical Study from Pre-Independence to the Merdeka Curriculum - Naila Nafahatus Sahariyah Al-Ulya; Is’ad Churiyah Zahidah; M. Yunus Abu Bakar (Jurnal Ilmiah Iqra', 2025)
The transformation of the Islamic Religious Education curriculum in Indonesia has undergone significant changes from the pre-independence period to the implementation of the Merdeka Curriculum. This study aims to analyze the development of the PAI curriculum through a socio-historical approach. Data collection was carried out through documentary studies. A qualitative approach was used in this research to explore the curriculum change process influenced by various social and historical factors. The analysis was conducted using curriculum transformation theories and sociological approaches to education. The findings of this study indicate that the PAI curriculum has evolved in line with the social and political dynamics in Indonesia, starting from the colonial era, independence, to the reform era, culminating in the Merdeka Curriculum. Factors such as the roles of key figures, government policies, and global influences have played a part in shaping the direction of this curriculum policy. The findings of this research provide insights into how the transformation of the PAI curriculum in Indonesia supports the development of character and religious understanding among the younger generation.